OBLIGATION OF THE HOST STATE TO ACT TRANSPARENTLY TOWARDS THE FOREIGN INVESTOR - Đundić, Petar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
Provisions on obligation of a host state to act transparently towards foreign investors increasingly often find their way into bilateral investment treaties. Their goal is to provide the investor with all information concerning the investment’s legal framework and which he needs in order to make an informed decision with regard to his investment. Certain provisions on transparency are so broad in their scope that they demand from the host state to provide an investor with a possibility to participate in the process of adoption of a state measure that could affect his interest. On the other hand, in arbitral practice the obligation to act transparently is traditionally seen as one of the elements of the fair and equitable treatment standard, although the practice has not so far provided a clear answer as to what is the exact role of this element and what is its relationship with other elements of the standard. The paper contains an analysis of transparency provisions from bilateral investment treaties concluded by the Republic of Serbia. The second part of the paper is dedicated to analysis of arbitral awards in which tribunals considered the transparency obligation as a part of the fair and equitable treatment standard.